2003
DOI: 10.4315/0362-028x-66.9.1564
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Escherichia coli O157 Contamination Routes in a Cattle Slaughterhouse

Abstract: In a cattle slaughterhouse, sampling was performed over a 1-week period to examine the prevalence and possible contamination routes of Escherichia coli O157. Each sampling day, swab samples were collected from the slaughterhouse environment before onset of slaughter, from the slaughterline, and from 20 successively slaughtered animals. Isolation of E. coli O157 consisted of a 6-hour enrichment followed by immunomagnetic separation and selective plating. From the 394 samples taken, 84 (21%) were positive for E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
41
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 19 publications
2
41
2
Order By: Relevance
“…Similarly, Small et al (26) recovered E. coli O157:H7, Salmonella, and Campylobacter in cattle lairages; E. coli O157:H7 was present in 27.2% of the lairage samples. E. coli O157:H7 can persist in lairage environments for several days and through cleaning periods (27). Few previous studies have addressed the issue of transport trucks as a source of E. coli O157: H7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Small et al (26) recovered E. coli O157:H7, Salmonella, and Campylobacter in cattle lairages; E. coli O157:H7 was present in 27.2% of the lairage samples. E. coli O157:H7 can persist in lairage environments for several days and through cleaning periods (27). Few previous studies have addressed the issue of transport trucks as a source of E. coli O157: H7.…”
Section: Discussionmentioning
confidence: 99%
“…McGee et al (19) found that within 24 h of introducing animals known to be shedding E. coli O157:H7 the hides of cohort animals became contaminated, and at 48 h 66% of the penmates had E. coli O157:H7 on their hides. In another study performed using molecular tracking methods, direct hide-to-hide contamination was a viable route for the transmission of E. coli O157:H7 during transport and lairage (27).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some authors have reported an optimal growth temperature for E. coli O157:H7 of around 40°C (31,44), and in recent studies workers have also used this temperature for incubation of enrichment cultures (1,2,32). However, there have been few studies in which the workers tried to compare the efficacies of different enrichment protocols, and the few results obtained have been different in different studies (21,39,42,58).…”
mentioning
confidence: 99%
“…These methods require an enrichment step to improve their limits of detection (8,25,39,58). Cui et al (20) reported that the PCR detection limit decreases from 3 log 10 CFU g Ϫ1 with no prior enrichment to 0 log 10 CFU g Ϫ1 with a 6-h enrichment step at 37°C.…”
mentioning
confidence: 99%
See 1 more Smart Citation